SOCIAL MEDIA FOR HOSPITAL MARKETING IN RURAL AREAS: PATIENT PERSPECTIVES OF A PRIVATE HOSPITAL - Yunita, Eva; Megawati, Devvy; Dewanto, Aryo (Universitas Brawijaya, 2025)
Social media has emerged as a widely utilized marketing tool across various industries globally, including the healthcare sector in Indonesia. It serves as a critical platform for hospital marketing; however, limited research has been conducted to examine its effectiveness, particularly in rural areas. This study aims to assess the potential and effectiveness of social media as a marketing tool for a private hospital in a rural setting. A qualitative research approach was employed, involving in-depth interviews with ten outpatients and inpatients at the selected hospital. Data were analyzed using thematic analysis, categorizing responses based on emerging themes. The findings indicated that WhatsApp was the most frequently used social media platform among patients, while patients’ families engaged with other platforms. Although social media platforms such as Instagram, TikTok, and Facebook were primarily used for entertainment, some respondents reported using them to obtain hospital-related information. The primary factors influencing hospital selection among patients were proximity to their residence and prior experience rather than information obtained through social media. The findings suggest that social media was not the primary source of information in patients’ decision-making processes regarding hospital selection. These insights may inform hospital management strategies in optimizing social media as a marketing tool to enhance patient engagement and outreach in rural healthcare settings.